Linking Phospholipid flippases to vesicle-mediated protein transport - Muthusamy, Baby-Periyanayaki (2009)
Type IV P-type ATPases (P4-ATPases) are a large family of putative phospholipid translocases (flippases) implicated in the generation of phospholipid asymmetry in biological membranes. P4-ATPases are typically the largest P-type ATPase subgroup found in eukaryotic cells, with five members in Saccharomyces cerevisiae, six members in Caenorhabditis elegans, 12 members in Arabidopsis thaliani and 14 members in humans. In addition, many of the P4-ATPases require interaction with a noncatalytic subunit from the CDC50 gene family for their transport out of the endoplasmic reticulum (ER). Deficiency of a P4-ATPase (Atp8b1) causes liver disease in humans, and studies in a variety of model systems indicate that P4-ATPases play diverse and essential roles in membrane biogenesis. In addition to their proposed role in establishing and maintaining plasma membrane asymmetry, P4-ATPases are linked to vesicle-mediated protein transport in the exocytic and endocytic pathways. Recent studies have also suggested a role for P4-ATPases in the nonvesicular intracellular trafficking of sterols. Here, we discuss the physiological requirements for yeast P4-ATPases in phospholipid translocase activity, transport vesicle budding and ergosterol metabolism, with an emphasis on Drs2p and its noncatalytic subunit, Cdc50p.